Analisis Perilaku Konsumtif melalui Online Shopping pada Remaja Muslim Desa Marga Mulya - Sefia Kurniasari; Hanna Hilyati Aulia; Suraya Murcitaningrum (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The development of digital technology and the ease of access to online shopping have encouraged changes in the consumption patterns of Muslim adolescents in Marga Mulya Village, leading to increasingly consumptive behavior. This condition is influenced by various factors, including digital promotions, social media, influencers, emerging trends, and peer environments that shape adolescents’ consumption patterns. This study aims to identify and analyze the forms of consumptive behavior among Muslim adolescents in online shopping activities and to examine their compatibility with Islamic values. The research employed a qualitative approach using a field research method. Data were collected through observation, interviews, and documentation. The informants consisted of Muslim adolescents who actively engage in online shopping activities. Data analysis was conducted descriptively through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the consumptive behavior of Muslim adolescents in Marga Mulya Village is reflected in purchasing goods due to discounts and promotions, the influence of social media and influencers, following trends, peer and lifestyle influences, and the desire to maintain appearance and self-image. These behaviors indicate that purchasing decisions are more strongly influenced by desires, social environments, and emotional factors rather than actual needs. From the perspective of Islamic values, most of these behaviors are not fully aligned with Islamic consumption principles, such as qana’ah (contentment), moderation (iqtisad), avoiding israf (excessiveness) and tabdzir (wastefulness), and prioritizing benefits as the basis of consumption. Nevertheless, some adolescents demonstrated consumption behavior that is more consistent with Islamic teachings by making purchasing decisions based on needs and the functional value of goods.